Pengembangan Permainan Edukasi guna Pengenalan Budaya Tak Benda di Indonesia berbasis Mobile - Setyo Nugroho; Ahmad Rio Adriansyah (Jurnal Informatika Terpadu, 2022)
The game "Ksatria Budaya" is an Android-based mobile game, designed as a medium for introducing Indonesian cultural heritage. This game uses Unity as a game engine and JSON as a database. This game is a combination of side scrolling game and quiz game. To see the feasibility of this game, the author will do 3 tests, namely black-box testing, compatibility testing, and usability testing. The development of this game begins with conducting a literature study related to research, culture and also the cultural heritage itself. Questions that appear in the game are based on data on the Ministry of Education and Culture website. The Agile SCRUM method was chosen by the author in the development of this game. The stages are carried out through creating user stories, designing product backlogs, sprint planning, sprints, and sprint reviews. The results of this game test are, all the functions in the game run well, the game can be installed and run on different devices, and gets a score of 83% for usability testing. Where if it is categorized by the score interpretation criteria table, this game is included in the very feasible criteria for use.